Pengaruh Model Pembelajaran Role Playing oleh Guru PAK Terhadap Minat Belajar Siswa Kelas V SDN 173525 Balige Kabupaten Toba Tahun Pembelajaran 2023/2024 - Monica Seles Situmorang; Ronny Simatupang; Helena Turnip; Dorlan Naibaho; Boho Parulian Pardede (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this research is to determine the positive and significant influence of the Role Playing learning model by PAK teachers on the learning interest of class V students at SDN 173525 Balige, Toba Regency, Academic Year 2023/2024. The method used in this research uses quantitative research methods. The population is all class V students of SDN 173525 Balige, Toba Regency, 2023/2024 academic year, totaling 40 people and all of them were used as research respondents. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Role Playing learning model by PAK teachers on the learning interest of class V students at SDN 173525 Balige, Toba Regency for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.580 > rtable(=0.05,n=40) = 0.312, thus it is known that there is a positive relationship between variable ,dk=n-2=38)= 2.021, thus there is a significant relationship between variable . b) Regression coefficient of determination test (r2) = 33.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=22, dk denominator=n-2=40-2=38) namely 19.27 > 1.51. Thus, Ha, namely that there is a positive and significant influence of the Role Playing learning model by PAK teachers on the learning interest of class V students at SDN 173525 Balige, Toba Regency, for the 2023/2024 academic year is accepted and H0 is rejected.